Implementasi Nilai Moral Melalui Pendekatan Afektif dalam Pembelajaran PAI Kelas IX di SMPN 8 Pamekasan - Suwantoro Suwantoro; Ayu Indang (Universitas Muhammadiyah Jember, 2021)
The implementation of a structured and programmed educational process in human life like a school is not only oriented to science, but also to the process of maintaining and enhancing moral quality. Therefore, it is important for every educational process at all levels to always consider and pay attention to the urgency of moral values that can be implemented in learning processes, especially in learning Islamic religious education. This research was conducted in a formal institution, namely SMPN 8 Pamekasan. In practice, researcher uses a qualitative approach with a descriptive type. The methods used to obtain data are interviews, observation, and documentation. There are at least two things to be examined in this research. First, how is the implementation of moral values through an effective approach in Islamic Education (PAI) learning for ninth grade students at SMPN 8 Pamekasan? The second is what are the supporting and inhibiting factors? The results of this study indicate that first, in practice, the teacher uses modeling by making himself the main example. There are five moral values implemented, namely religious values, discipline values, honest values, responsibility values , and communicative values. Second, the supporting factors are the implementation of extracurricular activities in the form of recitations every week, the approach of guardians, counseling teachers, and also student assistants. While the inhibiting factors are social environmental factors, the minimum portion or time of Islamic Education (PAI) subject in schools, and the latest in the development of increasingly sophisticated technology